2021
DOI: 10.1177/1759720x211006963
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, therapy and tumour response in patients with rheumatic immune-related adverse events following immune checkpoint inhibitor therapy: a single-centre analysis

Abstract: Background: Immune checkpoint inhibitors (ICIs) improved cancer therapy by inducing a higher immune system activity. This effect can cause rheumatic immune-related adverse events (rh-irAEs), which have not yet been extensively studied. Methods: We analysed 437 patients between 2014 and 2019, treated with ipilimumab (anti-CTLA-4) and/or nivolumab (anti-PD-1) or pembrolizumab (anti-PD-1) at the Clinic for Internal Medicine III, Oncology, Haematology and Rheumatology at the University Hospital Bonn, Germany. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…rh-irAEs include rheumatoid-like symptoms and rheumatic diseases, such as arthralgia, myalgia, arthritis, and tendinitis. However, symptoms of arthralgia and myalgia account for the majority of reports, and reports of the development of RF and anti-CCP-positive rheumatoid arthritis, as in this case, are rare (6)(7)(8). Patients with pre-existing autoimmune diseases (ADs) are largely ex-cluded from clinical trials of ICIs (9,10).…”
Section: Discussionmentioning
confidence: 98%
“…rh-irAEs include rheumatoid-like symptoms and rheumatic diseases, such as arthralgia, myalgia, arthritis, and tendinitis. However, symptoms of arthralgia and myalgia account for the majority of reports, and reports of the development of RF and anti-CCP-positive rheumatoid arthritis, as in this case, are rare (6)(7)(8). Patients with pre-existing autoimmune diseases (ADs) are largely ex-cluded from clinical trials of ICIs (9,10).…”
Section: Discussionmentioning
confidence: 98%
“…A blurred picture is starting to emerge, where we see a tendency for CTLA-4 blockade to induce gut affection more often than blockade of the PD-1 pathway. By contrast, PD-1 and LAG-3 blockade more often result in pneumonitis and joint affection ( 119 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate sensitivity was higher in the high-risk group, whereas the parthenolide and rapamycin sensitivity was lower in the high-risk group. Methotrexate is usually used for autoimmune disease therapy, and a single-center analysis reported that methotrexate has a good curative effect in rheumatic ir AEs (10). Parthenolide is one of the biologicals that play an anti-in ammatory role by inhibiting nuclear factor kappa B (NF-κB) and cytokine tumor necrosis factor (TNF)-α (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ir AEs may even lead to systemic infections and death, and an increase in fatal events has been reported (9). Corticosteroid therapy can successfully treat most ir AEs, but a combination of immunosuppressors is needed to combat more serious adverse reactions (10,11). However, since it is unclear whether a patient can undergo immunosuppressive therapy of ir AEs safely, there is an urgent need to nd some biomarkers to predict the drug sensitivity of immunosuppressors.…”
Section: Introductionmentioning
confidence: 99%